12-month randomised controlled trial of ginseng extract for moderate COPD. Issue 6 (2nd April 2019) - Shergis, Johannah Linda; Thien, Francis; Worsnop, Christopher John; Lin, Lin; Zhang, Anthony L; Wu, Lei; Chen, Yuanbin; Xu, Yinji; Langton, David; Da Costa, Cliff; Fong, Harry; Wu, Darong; et al.
Abstract : Background: Panax ginseng (ginseng) is a therapeutic herb which might be beneficial in COPD. The study investigated if ginseng, compared with placebo, is effective and safe for people with moderate COPD. Methods: This multicentre, randomised, double-blind, placebo-controlled trial compared 24 weeks of ginseng capsules (100 mg twice daily) with placebo. Participants were followed up for a further 24 weeks. Participants were aged 40 years and over and had airflow limitation in the moderate (Global Initiative for Chronic Obstructive Lung Disease 2) COPD range. The coprimary endpoints were the St George's Respiratory Questionnaire, the COPD Assessment Test and the Short Form Health Survey. Secondary outcomes included lung function, exacerbation rate and use of relief medication. Findings: 168 participants were randomised 1:1 from five centres in Australia and China. Baseline characteristics were balanced between groups. There were no significant differences between ginseng and placebo, with overall results improving in both groups. Ginseng seemed safe for, and well tolerated by, people with COPD. Interpretation: There was no significant difference in improvement in health-related quality of life (primary outcome) between the ginseng and placebo groups. Trial registration number: ACTRN12610000768099.